Contribution of miRNAs and Other Inflammatory Biomarkers to the Differentiation of Inflammatory and Non-Inflammatory Joint Effusions - Kušnierová, Pavlína; Bystroňová, Iveta; Walder, Pavel; Hlubek, Rudolf; Stejskal, David (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2021)
PURPOSE OF THE STUDY The aim of the study was to determine miR-146a-5p, miR-223-3p and miR-23a-3p by an enzyme immunoassay in patients with inflammatory and non-inflammatory joint effusion and to verify the usefulness of these miRNAs as biomarkers of joint inflammation. MATERIAL AND METHODS Synovial fluid (SF) samples were collected from 82 patients. The group consisted of 60 non-inflammatory, 11 inflammatory-non-pyogenic, 11 inflammatory-pyogenic SF. SF miRNA was isolated by RNA Isolation Kit Plasma/Serum. The concentrations of miRNA were determined by enzyme-linked immunosorbent assays (ELISA), C-reactive protein, interleukin-6 and procalcitonin on automatic analyser, presepsin on POCT system, interleukin-1 and human neutrofil defensins 1-3 by ELISA. RESULTS A statistically significant negative correlation was found between miR-146-5p and miR-223-3p, WBC, IL-1β, IL-6 and CRP (P < 0.05) in all groups; a statistically significant positive correlation was found between miR-223-3p and miR-23a-3p, WBC, PMN, IL-1beta, IL-6 and HNP1-3, as well as a positive correlation of miR-23a-3p with IL-1β, IL-6 and HNP1-3. A statistically significant difference was found between miR-146a-5p, miR-223-3p and miR-23a-3p and individual SF groups, P = 0.006, P < 0.001, respectively. PMN, WBC, Il-1β, IL-6, HNP 1-3 predicted the inflammatory processes with excellent diagnostic power (AUC > 0.9). The clinical relevance expressed by effect size was the strongest in miR-223-3p, PMN, IL-1 , HNP 1-3 between non-inflammatory and inflammatory-pyogenic group. CONCLUSIONS Our study quantified the SF miRNA by ELISA. We have shown that miR-146a-5p, miR-223-3p and miR-23a-3p can be an important group of biomarkers for the detection and monitoring of various pathophysiological conditions in synovial fluid, including inflammatory conditions. Key words: miRNA, synovial fluid, inflammatory joint disease, enzyme-linked immunosorbent assay.
Keywords: Lipopolysaccharide Receptors; Humans; biologické markery; MicroRNAs; Biomarkers; peptidové fragmenty; lipopolysacharidové receptory; Peptide Fragments; mikro RNA; lidé